SERS-based assay for multiplexed detection of cross-reactivity and persistence of antibodies against the spike of the native, P.1 and B.1.617.2 SARS-CoV-2 in non-hospitalised adults. Issue 4 (28th June 2022) - Chisanga, Malama; Stuible, Matthew; Gervais, Christian; L'Abbé, Denis; Cass, Brian; Bisson, Louis; Pelletier, Alex; Lord-Dufour, Simon; Durocher, Yves; Boudreau, Denis; Trottier, Sylvie; Pelletier, Joelle N.; et al.
Abstract : Monitoring antibody response to SARS-CoV-2 is critical for assessing the humoral response, especially important considering the emergence of multiple SARS-CoV-2 variants of concern (VOCs). Abstract : Monitoring antibody response to SARS-CoV-2 is critical for assessing the humoral response, especially important considering the emergence of multiple SARS-CoV-2 variants of concern (VOCs). Herein, we developed rapid and highly sensitive microfluidics-integrated multiplexed SERS to simultaneously screen multiple anti-spike immunoglobulin isotypes (IgG, IgA and IgM) to establish the level of cross-reactivity and the persistence of anti-spike immunoglobulins in immune patient sera for the native, P.1 and B.1.617.2 strains of SARS-CoV-2 virus. The study was performed on 24 non-hospitalised adults with laboratory diagnosed COVID-19 and had fully recovered before the emergence of the P.1 and B.1.617.2 mutants. We report seroconversion and cross-protection of IgG, IgA and IgM antibodies against the spike proteins of the native SARS-CoV-2, and the P.1 and B.1.617.2 VOCs in sera collected longitudinally at 3 weeks and 8 weeks following a PCR-positive test. Although high levels of IgG, IgA and IgM were detected against the native strain, immune responses of cross-reactive binding antibodies against the spike protein of the VOCs decreased significantly. Our study revealed that in addition to exhibiting the highest seropositivity rates (>97%), IgG responses were maintained up to 8 weeks post-diagnosis, irrespective of the tested spike protein. In contrast, the relatively high seropositivity rates of IgA and IgM (>86% and >80%, respectively) detected at 3 weeks post diagnosis decayed rapidly, approaching baseline by week 8 post-diagnosis, and this observation was congruent with binding affinities of IgA and IgM. We also demonstrate that the levels of anti-spike antibodies correlated with patient age, with the oldest individuals (>70 years) displaying highest antibody binding responses across the spike antigens. Collectively, our results illustrate the potential applicability of multiplexed SERS assays to screen past COVID-19 and to assess cross-protective humoral immunity against VOCs.